(untitled) (VITAE Academia Biomédica Digital, 2021)
The research aimed to evaluate the antioxidant effect of an organic aqueous extract of green tea (Camellia sinensis), by inducing an oxidative stress with hydrogen peroxide (H2O2) to Saccharomyces cerevissiae. Materials and methods: Green tea leaves were used to obtain the aqueous extract. Prior to the evaluation of the extract, the concentration of phenolic compounds was determined by the Folin-Ciocalteu method. For the evaluation of the antioxidant capacity, the biological model of S. cerevissiae was used. Results: The concentration of total phenolic compounds in the extract was 216.23±2.13 mg of GAE / g PM. In the evaluation of the antioxidant activity, a marked inhibitory effect of the oxidative stress in the presence of H2O2 was observed. Conclusion: the high content of bioactive compounds present in C. sinensis, represent an alternative in the treatment and prevention of diseases linked to a high expression of reactive oxygen species.